Next generation performance status: digital health technologies across the lung cancer continuum - Scarpa, Julia; Hussain, Iqram; Cheng, Alex; Villena-Vargas, Jonathan; Boyer, Richard (Frontiers in Digital Health, 2025)
Lung cancer survival rates have greatly benefited from recent advances in therapies and screening. New digital health technologies offer clinicians another way to personalize and enhance care for these patients. For example, emerging technologies support continuous assessment of patients' functional capacity and provide real-time health feedback, improving management of chronic symptoms and monitoring of health trajectory. This review explores these advancements and their potential applications across the lung cancer continuum.